Acute Stroke due to Vertebral Artery Dissection in Giant Cell Arteritis - Marte Furment, Marlene; Antigua Jimenez, Sandra; Pabolu, Sangeetha (Case Reports in Rheumatology, 2021)
The diagnosis of giant cell arteritis (GCA) when presenting with atypical features such as stroke is very challenging. Only 0.17% of first-ever strokes are caused by GCA, a life-threatening condition when left untreated. Very few cases have been reported on giant cell arteritis leading to acute stroke due to vertebral artery dissection. We present a case of a 76-year-old female with no medical history who presented with sudden onset right visual loss and left hemiparesis. She had been initially treated for acute stroke and upon further workup was found to have left vertebral artery dissection. She had erythrocyte sedimentation rate (ESR) of 71 mm/h, and bilateral temporal artery biopsy was consistent with giant cell arteritis. Patient received high doses of methylprednisolone which resolved her hemiparesis, but her vision loss did not improve. Stroke in the presence of significant involvement of vertebral arteries should raise suspicion of GCA especially if classic symptoms preceded stroke event. High clinical suspicion is required to prevent delay in diagnosis and treatment.